Epidemiology of nursing home dialysis patients—A hidden population. Issue 4 (16th June 2021) - Bellin, Eran Y.; Hellebrand, Alice M.; Kaplan, Steven M.; Ledvina, Jordan G.; Markis, William T.; Levin, Nathan W.; Kaufman, Allen M.
Abstract: Introduction: Dialysis patients are often discharged from hospitals to skilled nursing facilities (SNFs), but little has been published about their natural history. Methods: Using electronic medical record data, we conducted a retrospective cohort study of nursing home patients treated with in‐SNF hemodialysis from January 1, 2018 through June 20, 2020 within a dialysis organization across eight states. A dialytic episode began with the first in‐SNF dialysis and was ended by hospitalization, death, transfer, or cessation of treatment. The clinical characteristics and natural history of these patients and their dialytic episodes are described. Findings: Four thousand five hundred and ten patients experienced 9274 dialytic episodes. Dialytic episodes had a median duration of 18 days (IQR: 8–38) and were terminated by a hospitalization n = 5747 (62%), transfer n = 2638 (28%), death n = 568 (6%), dialysis withdrawal n = 129 (1.4%), recovered function n = 2 (0.02%), or other cause n = 6 (0.06%). Increased patient mortality was associated with advancing age, low serum creatinine, albumin, or sodium, and low pre‐dialytic systolic blood pressure (sBP). U‐shaped relationships to mortality were observed for intradialytic hypotension frequency and for post‐ > pre‐hemodialysis sBP frequency. Prescription of dialysis five times weekly in the first 2 weeks was associated with better survival in the first 90 days (HR 0.77, CI 0.62–0.96; p < 0.02). Discussion: Provision of in‐SNF dialysis by an external dialysis organization enables discharge from the acute care setting for appropriate treatment with increased nursing contact time in an otherwise under‐resourced environment. SNF ESRD patient clinical characteristics and outcomes are extensively characterized for the first time.